2008
DOI: 10.1111/j.1745-493x.2008.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Alignment and Purchasing Efficacy: An Exploratory Analysis of Their Impact on Financial Performance

Abstract: Purchasing and supply management (PSM) has become a discipline of major strategic importance for effectively competing in today's global marketplace. Literature recognizes that the full value‐creation potential of the purchasing function can only be realized if its decisions and activities are aligned with the organization's overall strategic orientation. Despite general agreement on this matter, research and practice lacks knowledge on how exactly such an alignment can be achieved and what performance implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0
22

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(175 citation statements)
references
References 77 publications
(159 reference statements)
0
153
0
22
Order By: Relevance
“…The impact of supply management on the firm's performance has frequently been discussed in the past (Chen, Paulraj, and Lado 2004;Bernardes and Zsidisin 2008;Baier, Hartmann, and Moser 2008). However, we note that the performance impact of the purchasing structure has only infrequently been studied thus far.…”
Section: Performance Impact Of the Purchasing Organizationmentioning
confidence: 99%
“…The impact of supply management on the firm's performance has frequently been discussed in the past (Chen, Paulraj, and Lado 2004;Bernardes and Zsidisin 2008;Baier, Hartmann, and Moser 2008). However, we note that the performance impact of the purchasing structure has only infrequently been studied thus far.…”
Section: Performance Impact Of the Purchasing Organizationmentioning
confidence: 99%
“…Avram and Kahne (2008) argued that firms could charge a premium for their CSR-oriented approaches. The sustainable products" market positioning could be improved through the use of social responsibility and responsible supply chain management (Palazzo and Basu, 2007), There are positive implications for certain firms that pursue differentiation strategies (through social and environmentally responsible practices) as a means to signal an image of high product quality and sustainability to consumers (Tate et al, 2010), As a matter of fact, numerous findings reported how socially responsible business practices are actually improving both brand equity and organisational performance (Lai, Chiu, Yang, and Pai, 2010;Castaldo, Perrini, Misani and Tencati, 2009), On the other hand, some other contributions have indicated that there is little evidence on socially responsible firms that pursue niche strategies in narrow markets (Van De Ven and Jeurissen, 2005;Weitzner and Darroch, 2010), It may appear that the supply chain literature has often ignored how niche firms develop their supply chain strategies (Baier et al, 2008;13 Cousins, 2005), Perhaps, it may prove difficult for academia to propose a specific relationship between niche strategy and socially responsible supply chain management. The responsible procurement of materials and products may not necessarily constitute a part of the firms" strategy.…”
Section: The Link Between Responsible Supply Chain Management and A Dmentioning
confidence: 99%
“…The engagement with suppliers is stronger and deeper when the firms pursue differentiation strategies (Porter and Kramer, 2006), González-Benito (2007) found that the fit between business strategy and purchasing strategy significantly moderates the relationship between purchasing efficacy (as measured by the fit between purchasing strategy and capabilities, and firm performance), It may appear that focal firms invest in building relationships with suppliers in order to improve their effectiveness and to gain potential collaborative advantages (Hoejmose et al, 2013), Interestingly, Baier, Hartmann and Moser (2008) noticed that innovative firms were emphasising on supplier management, talent management, integration and core processes; as they compared them to low-cost firms that were more focused on information and knowledge management (rather than cross-functional collaboration), Very often, the low-cost producers consider the supply chain as a source of cost savings and invest less in supplier development (Hoejmose et al, 2013),…”
Section: The Link Between Responsible Supply Chain Management and A Dmentioning
confidence: 99%
“…Strategic procurement strategies have been recognised as essential in the age of global competitiveness (Baier, Hartmann, & Moser, 2008), yet most procurement research and the extant literature tends to promote the concept that economic gain, through cost reductions, provides suitable impetus for new policies. The contention of this chapter is sharply different: carefully designed strategic procurement policies can promote local sourcing, expanding local customer bases, and increasing market opportunities locally.…”
Section: Government and Poverty In The Communitymentioning
confidence: 99%